2016
DOI: 10.11606/issn.2525-376x.v1i2p5-12
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Engineering and Operations Research: A Passing Flirtation or Marriage?

Abstract: Since the 1980's, the technological partnership between Petrobras and the University of São Paulo (USP) in the field of industrial automation has been prolific in double lane. Relevant scientific and technological contributions have continuously been produced within several related chemical engineering (ChE) disciplines. Among the latest results from this fertile collaboration is the exciting discipline Optimization Applied to Operations Management in the Chemical Industry which now is part of the USP undergra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The IMF also provide graphical user interface prototypes for drawing the flowsheet and typical Gantt charts and trend plots to view the solution of quantity, logic and quality timeprofiles. Lessons learned and the importance of education in PSE and related areas as operations research can be found in Joly et al (2015), Joly and Gut (2016) and .…”
Section: Introductionmentioning
confidence: 99%
“…The IMF also provide graphical user interface prototypes for drawing the flowsheet and typical Gantt charts and trend plots to view the solution of quantity, logic and quality timeprofiles. Lessons learned and the importance of education in PSE and related areas as operations research can be found in Joly et al (2015), Joly and Gut (2016) and .…”
Section: Introductionmentioning
confidence: 99%